A193 TIMELY HEPATITIS B IMMUNIZATION OF THE AT-RISK NEONATE: A QUALITY ASSURANCE REVIEW. (15th March 2019) - Azzopardi, P; Ly, L; Azzopardi, P; DiGravio, B; Roy, M; Brill, H
Abstract: Background: Hepatitis B is an infectious disease that affects approximately 257 million people worldwide and is ranked as the fourth most burdensome pathogen in Ontario, with clinical sequelae including liver cirrhosis, organ failure, and cancer. Although Ontario offers routine hepatitis B vaccination in adolescence, infants born to infected mothers remain at risk due to vertical transmission of the virus during childbirth. This necessitates routine HBsAg screening in the first trimester of pregnancy. According to the Canadian Immunization Guide (CIG), all infants born to HBsAg+ mothers should receive hepatitis B immune globulin (HBIg) and vaccine within 12 hours of age. It is unclear whether these measures are administered in a timely manner. Aims: The purpose of this study was to retrospectively review the time to administer HBIg and vaccine for infants born to HBsAg+ mothers. Methods: Following REB approval, mother-infant charts were selected by identifying orders for hepatitis B vaccine in infants between 2010 and 2015. Mother-infant dyads were excluded if the mother was HBsAg- or status unknown. Paired charts were retrospectively reviewed at 6 hospital sites in Ontario including 2 community hospitals, 2 academic hospitals, and 2 affiliated teaching hospitals. Non-parametric analysis of variance (ANOVA) and correlation tests were run at a significance of p<0.05. Results: 460 mother-infant dyads were included for full chart review across 6 hospital sites. The mean vaccination time was 5.0 hours (95% CI [4.4, 5.2]) with significant differences between sites (WF5, 58 =21.3, p<0.001, η 2 = 0.31). The mean time of HBIg administration was also 5.0 hours (95% CI [4.5, 5.2]) with significant differences between sites (Welch's F5, 61 =18.7, p<0.001, η 2 = 0.23). 23 infant charts (5.0%) documented late hepatitis B vaccination and 22 infant charts (4.8%) documented late HBIg administration, with 2.4% of at-risk infant charts documenting both late vaccine and HBIg administration. On average, infants born to married mothers were vaccinated earlier (x=-65 mins). Early morning delivery (2400-0800) tended to result in later vaccination times (x=+66 mins). 10.8% of at-risk infant charts had at least one undocumented time of HBIg or vaccine administration. Conclusions: At-risk newborns for the vertical transmission of hepatitis B infrequently encounter immunization delays, including the late administration of HBIg or vaccine within the first 12 hours of life. A focus on standardizing care pathways regardless of site or time of delivery may help to improve the timeliness of hepatitis B immunization. Further study could explore the cost-benefits of universal neonatal hepatitis B immunization. Funding Agencies: None